Pengembangan Media Posse (Poster Sejarah) untuk Melatih Analisis Berpikir Kronologis Siswa SMA dalam Pembelajaran Sejarah - Putri, Dini Eka; Hastuti, Hera (Jurusan Sejarah FIS UNP, 2025)
This research is motivated by the low level of chronological thinking skills among students at SMA Negeri 5 Solok Selatan, causing them difficulty in understanding the sequence of time in historical events, even though history is closely related to time. Moreover, history teachers only use powerpoint, printed textbooks, and student worksheets (lks) that are dominated by text as the main media in history learning. This study aims to determine the development procedure and analyze the feasibility, practicality, and effectiveness of the posse media (poster sejarah) to train students' chronological thinking analysis in high school history learning. The method used in this study is Research and Development (R&D) with the ADDIE model. Data analysis techniques used both qualitative and quantitative approaches with measurements based on the Likert Scale. The results of this study show: (1) The development procedure of posse (poster sejarah) begins with the analysis stage, design stage, development stage, implementation stage, and evaluation stage. (2) The feasibility of posse media (poster sejarah) based on validation tests by material and media expert validators falls into the very feasible category with an average score of 3.89 for material and 3.62 for media. (3) The practicality of posse media (poster sejarah) is in the very practical category with a score of 4.00 from the history teacher and 3.86 from students. (4) The effectiveness test of posse media (poster sejarah) based on interviews with the history teacher and six students shows that this media is very effective. It can be concluded that the posse media (poster sejarah) is highly feasible, practical, and effective for training high school students’ chronological thinking analysis.